2008
DOI: 10.1097/brs.0b013e31815e5dce
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Kinematics of Two Types of Ball-and-Socket Cervical Disc Replacements in the Sagittal Plane

Abstract: Neither the cranial or caudal types of ball-and-socket designs did fully restore the normal mobility in terms of ROM and COR in this patient's series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…In normals, the location of the COR is reported to be significantly more cranial as the level progresses from C3 to C7 [17,30]. The average COR location in the AP direction, however, does not change significantly with level [17,30]. When we compared the COR at the CDR-level with the supra-adjacent normal levels, our study showed that only the COR-X was significantly different, while the COR-Y was not.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In normals, the location of the COR is reported to be significantly more cranial as the level progresses from C3 to C7 [17,30]. The average COR location in the AP direction, however, does not change significantly with level [17,30]. When we compared the COR at the CDR-level with the supra-adjacent normal levels, our study showed that only the COR-X was significantly different, while the COR-Y was not.…”
Section: Discussionmentioning
confidence: 82%
“…Translation was not different to the fusion group. In the study of Rousseau [30] the ROM at CDR level was significantly less than in normals (13.4°) using the Prestige LP (5.1°) or the Prodisc-C disc (3.6°). Finally, in a study by Picket [27] using QMA in 20 patients with 1-or 2-level surgery with the Bryan disc at C5-C7, follow-up 6-24 months, ROM was 8.9°at the CDR-level and not significantly different to the preoperative measures.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations